The rectus abdominus myoperitoneal flap for vaginal reconstruction - Vishaal Gupta; Genevieve K. Lennox; Allan Covens (Elsevier, 2020)
To review the indications, technique and results of the rectus abdominis myoperitoneal (RAMP) flap for vaginal reconstruction from literature and at a single institution. A literature search was conducted of vaginal reconstruction to identify published cases using RAMP flaps. All cases of vaginal reconstruction at Sunnybrook Health Sciences Center (SHSC) from 2007 to 2019 were reviewed. Twenty-one published cases of vaginal reconstruction with RAMP flaps were identified. Eleven had partial longitudinal vaginal defects, 5 had circumferential defects and 5 had unspecified defects. Eight patients with circumferential (N = 3) or unspecified (N = 5) defects developed vaginal stenosis. None of the 11 patients with partial longitudinal defects developed vaginal stenosis and 8 resumed sexual activity. There were 2 cases of donor site hernia and 4 donor site infections, but no flap loss. At SHSC, 5 cases of RAMP flap vaginal reconstruction were identified. Cases 1-3 and 5 had circumferential vaginal defects and Case 4 had a partial longitudinal defect. There were no cases of flap necrosis or donor site hernia. Case 1 died 18 days after pelvic exenteration from bowel ischemia. Case 2 developed a rectovaginal fistula after an anastomotic leak from a low anterior resection. Case 3 had a wound infection and vaginal shortening to 3-4 cm. Cases 4 and 5 had no complications and the vagina appeared normal on exam post-operatively. The literature and our experience support the use of RAMP flaps for reconstruction of partial longitudinal vaginal defects but not circumferential defects where the risk of vaginal stenosis and shortening is high.